Comparing generators for language-based tools - Cruz, Daniela (2007)
The first step in any language development project is the Compiler Generator choice. Nowadays there are many offers, based on translation grammars, attribute grammars or other language specification formalisms. To make up a decision, more factors than just the tool user-friendliness and the processor’s quality should be taken into account. To aid the language developer, we analyze in this paper three Compiler Generators. The traditional and well known YACC, and two more recent ones, LISA and AnTLR-3. The first produces a Syntax-Directed Translator, while the others generate a Semantic-Directed Translator based on attribute evaluation. Moreover both the AG-based generators also produce other Language-based Tools that are mentioned and compared.